Determining the laminar burning velocity of nitrogen diluted dimethoxymethane (OME1) using the heat‐flux burner method: Numerical and experimental investigations. (11th October 2020) - Eckart, Sven; Fritsche, Chris; Krasselt, Cornelius; Krause, Hartmut
Summary: Premixed flames play a prominent role in combustion systems such as aircraft combustors, gas turbines and internal combustion engines. Current fuels are also derived from fossil sources, including coal, petrol, gasoline, natural gas or liquefied petroleum gas. Alternatively, liquid and gaseous biofuels, such as ethanol and biodiesel, hydrogen, wood gas or coal gas, can be used with appropriate modifications. Furthermore, the components of oxygenated fuel are known for their reduction of soot particles in diesel combustion processes while having little effect on nitrogen oxide (NOX ) emissions. The advantage of C1 ‐oxygenate dimethoxymethane (OME1, also called "methylal" or DMM) is the lack of CC bonds in their molecular structure. OME1 belongs to the group of oxymethylene ethers (OMEn ) with the molecular structure CH3 O(CH2 O)n CH3 where n = 1 (short molecular structure: C3 H8 O2 ). This experimental and numerical study aims to investigate the laminar burning velocity (LBV) of the oxymethylene ether (OMEn, n = 1), the influence of temperature and nitrogen dilution. To our knowledge, no studies have been conducted with regards to nitrogen dilution during the measurements of OME1 burning velocity. In this study, a heat‐flux burner setup was used to investigate the LBV for equivalence ratios from 0.7 to 1.6. The experimental LBV data shows a decreasing nonlinear influence of nitrogen dilution effects for 0% to 70% and increasing linear with preheating up to 373 K. The numerical results were compared with the experiments conducted with simple alcohols (ethanol) and C3 hydrocarbon fuels (propane). Existing numerical reaction mechanisms can only partially reproduce the new experimental data. Finally, a sensitivity analysis was conducted by changing various parameters during the numerical investigations, in order to clarify the discrepancy. Abstract : In this work, the heat‐flux method is used to investigate the laminar burning velocity of the oxygenated fuel OME1 /DMM. The fuel is experimentally and numerically compared to laminar burning velocity of propane, ethanol and other oxygenated fuels and the influence of temperature and nitrogen admixture is investigated. OMEs are in general more resistant to changes of the equivalence ratio than hydrocarbons and have their maximum laminar burning velocity above those fuels.